Towards an Understanding of the Conceptual Evaluation in Physical Education - Toro-Arevalo, S (UNIV NAC LA PLATA, FAC HUMANIDADES & CIENCIAS EDUC, 2019)
Knowledge, in its conceptual dimension, is the type of "knowledge" that has usually been linked from the different subjects that make up the school curriculum, except in Physical Education. From this perspective, the objective of this paper is to understand the meaning that Physical Education teachers give to conceptual evaluation. An investigation was carried out with a qualitative approach and as a data collection technique, the semi-structured interview was performed. The stories were analyzed and categorized under the content analysis technique. Twelve teachers from different administrative units of Llanquihue s Province, Region of Los Lagos, took part. The most relevant results show, on the one hand, conceptual confusion in the discipline, framed in the functional character of the evaluation, measurement and qualification and, on the other, Physical Education teachers recognize important benefits of the conceptual evaluation in the discipline. Nevertheless, most of the teachers interviewed continue to carry out evaluations oriented towards the procedural dimension (know-how). In this sense, it is possible to conclude the existence of a classification of the evaluation with aims pointed at controlling objectives and learning.